Who continued travelling by bus in different periods of COVID-19? A data-driven analysis from Shanghai, China - Weihan Bi; Yu Shen; Yuxiong Ji; Yuchuan Du (PLoS ONE, 2025)
The COVID-19 pandemic has caused unprecedented disruptions to individual travel behavior in the public transport (PT) system. To attract more travelers to use PT in the post-pandemic era, it is necessary to understand the heterogeneity of travel behavior changes among various user segments and across different pandemic periods. This paper presents a two-step analysis framework for discovering the inter-segment and intra-segment changes in travel patterns of PT users based on ticketing data. The framework is then applied to the case of Jiading bus transit in Shanghai, China during the COVID-19 pandemic in 2022. The results suggest that commuters are more vulnerable to the impacts of the pandemic than non-commuters, with a considerable tendency to give up commuting by bus or even permanently discontinue bus usage after the lockdown in Shanghai. Only 17.7% of bus users maintain their travel patterns after the lockdown, with a few observable sub-segments of users comprising students and employees. The findings in this study aid PT operators in achieving a better recovery in the post-pandemic era and enhance their preparedness to tackle challenges in demand management for potential crises.